National governance for development: International experiences and reference values for Vietnam in the new era - NGUYỄN QUỐC SỬU (Political Theory Journal, 2026)
The article employs literature analysis, academic comparison, and synthesis of international experiences to clarify the emergence, characteristics, pillars, and operational mechanisms of national governance for development within the theoretical frameworks of the World Bank (WB), UNDP, OECD, and other prominent studies. On this basis, it suggests policy implications for Vietnam through a systemic governance reform approach, relocating the state’s developmental role, prioritizing the enhancement of policy coordination and implementation capacities, promoting result-based management, expanding social participation, and aligning digital transformation with institutional improvement to foster sustainable development goals.